Governance Developments in Challenge Situations: A Case Study of the Governance in Aceh after 2005 Helsinki Memorandum of Agreement - Hassanudin; Muhadjir Muhammad Darwin; Irwan Abdullah; Agus Heruanto Hadna (International Journal of Science and Society, 2023)
This study explored about the Governance Developments in Challenge Situations in Aceh after 2005 Helsinki Memorandum of Agreement. The 2005 Helskinki Memorandum of Agreement brings promise into welfare and better governance for Aceh people. However, there are problems such as welfare and governance (corrupt leaders). First, the problem of socio-economic development in Aceh after the Helsinki agreement apparently occurred not at the stage of regulation and budget support, but at the leadership stage. Second, leadership problems have persisted even though elections have been held. This is an indication of elite problems in governance in Aceh. These two backgrounds form the basis for this article to discuss the main issue of Why Aceh's Governance after Helsinki Memorandum of Understanding in 2005 has not run optimally in providing for the needs of the Acehnese people. Using quantitative and qualitative methods, this article provides the relations between political elites on good public governance. Academically, this article will be able to provide a new dimension of form of relations between political elites on good public governance. Practically, this article can provide recommendations on the form of relations between political elites that affect good public governance in the success of the Aceh Government's development programs.